Anti-Inflammatory and Antioxidant Properties of a New Mixture of Vitamin C, Collagen Peptides, Resveratrol, and Astaxanthin in Tenocytes: Molecular Basis for Future Applications in Tendinopathies - Monica Marzagalli; Stefania Battaglia; Michela Raimondi; Fabrizio Fontana; Marco Cozzi; Francesca R. Ranieri; Roberto Sacchi; Valeria Curti; Patrizia Limonta (Mediators of Inflammation)
Tendinopathy is one of the most frequent musculoskeletal disorders characterized by sustained tissue inflammation and oxidative stress, accompanied by extracellular matrix remodeling. Patients suffering from this pathology frequently experience pain, swelling, stiffness, and muscle weakness. Current pharmacological interventions are based on nonsteroidal anti-inflammatory drugs; however, the effectiveness of these strategies remains ambiguous. Accumulating evidence supports that oral supplementation of natural compounds can provide preventive, and possibly curative, effects. Vitamin C (Vit C), collagen peptides (Coll), resveratrol (Res), and astaxanthin (Asx) were reported to be endowed with potential beneficial effects based on their anti-inflammatory and antioxidant activities. Here, we analyzed the efficacy of a novel combination of these compounds (Mix) in counteracting proinflammatory (IL-1β) and prooxidant (H2O2) stimuli in human tenocytes. We demonstrated that Mix significantly impairs IL-6-induced IL-1β secretion, NF-κB nuclear translocation, and MMP-2 production; notably, a synergistic effect of Mix over the single compounds could be observed. Moreover, Mix was able to significantly counteract H2O2-triggered ROS production. Together, these results point out that Mix, a novel combination of Vit C, Coll, Resv, and Asx, significantly impairs proinflammatory and prooxidant stimuli in tenocytes, mechanisms that contribute to the onset of tendinopathies.